Kemampuan Penalaran Matematis Siswa SMA Dalam Menyelesaikan Masalah Tiga Dimensi - Yodiatmana Yodiatmana; Atma Murni; Nahor Murani Hutapea (Universitas Maritim Raja Ali Haji, 2023)
The purpose of this study was to describe students' high initial ability, moderate initial ability, and low initial ability mathematical reasoning abilities. The reality in the field shows that students' mathematical reasoning skills in 3D materials are still low and still need to be improved. The subjects in this study were class XII students of SMKF Pekanbaru City totaling 32 students, Riau Province. The research method uses a qualitative descriptive approach. Data collection techniques using written tests, documentation, and interviews. Data analysis using qualitative descriptive analysis by preparing and organizing various kinds of student error data based on each indicator of mathematical reasoning. The results of the research on students' mathematical reasoning ability on each indicator in order are; (1) Presents mathematical statements in pictures 83.3%; (2) Provide reasons or evidence for one or more solutions 55.6%; (3) Make a guess 61.1%; (4) Draw conclusions from statements 63.9%; (5) Checks the validity of an argument 73.6%; and (6) drawing conclusions from several statements 56.5%. The results of this study indicate that mathematical reasoning ability in 3D material in this study 4 indicators are still classified as low. while 2 of them are classified as high.